Saccharomyces Rrm3p, a 5′ to 3′ DNA helicase that promotes replication fork progression through telomeric and subtelomeric DNA - Ivessa, Andreas S. (Cold Spring Harbor Laboratory Press, 2002)
In wild-type Saccharomyces cerevisiae, replication forks slowed during their passage through telomeric C(1–3)A/TG(1–3) tracts. This slowing was greatly exacerbated in the absence of RRM3, shown here to encode a 5′ to 3′ DNA helicase. Rrm3p-dependent fork progression was seen at a modified Chromosome VII-L telomere, at the natural X-bearing Chromosome III-L telomere, and at Y‘-bearing telomeres. Loss of Rrm3p also resulted in replication fork pausing at specific sites in subtelomeric DNA, such as at inactive replication origins, and at internal tracts of C(1–3)A/TG(1–3) DNA. The ATPase/helicase activity of Rrm3p was required for its role in telomeric and subtelomeric DNA replication. Because Rrm3p was telomere-associated in vivo, it likely has a direct role in telomere replication.